Pengembangan Media Pembelajaran Interaktif Untuk Materi Pelajaran Pemrograman Dasar Kelas X di SMK Negeri 8 Malang Menggunakan Model APPED - Samsul Arifin; Hanifah Muslimah Az-Zahra; Admaja Dwi Herlambang (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
In the Software Engineering (RPL) class X of SMK Negeri 8 Malang, it can be seen that the learning process is still conventional so students cannot understand basic programming materials, students have difficulty learning independently because they do not have learning resources. So it is necessary to conduct research on Interactive Learning Media Development for Class X Basic Programming Subjects at SMK Negeri 8 MALANG Using the APPED Model. The APPED research model has 5 steps: initial analysis and research, design, production, evaluation and dissemination. The results of ongoing evaluations with three aspect criteria get valid results. At the alpha testing stage the material validator obtained a value of 70.00 in the "good" category, 72.00 in the "good" category by the media validator, and a value of 92.00 in the "very good" category by the instructor validator. The results of beta testing conducted on 3 students based on the level of student ability on an average pretest obtained by 70%, while the average posttest results obtained by 86.6% so that there is an increase in student learning outcomes. The normality test results have normal distribution data with sig> 0.05. The standard deviation results are 9.21, the significance results are 0.00, so it is concluded that at the level of sig there are differences. Based on the results of different trials conducted, the interactive learning media can be disseminated.